Cover Image, Volume 16, Issue 3. (25th May 2022) - Phillips, Steven D.; Jones, Susanne B.; Meyer, Pimphan A.; Snowden‐Swan, Lesley J.
Abstract: The cover image is based on the Research Article Techno‐economic analysis of cellulosic ethanol conversion to fuel and chemicals by Steven Phillips et al., https://doi.org/10.1002/bbb.2346 . Abstract : The cover image is based on the Research Article Techno‐economic analysis of cellulosic ethanol conversion to fuel and chemicals by Steven Phillips et al., https://doi.org/10.1002/bbb.2346 .